Análise e proposição de estratégias projetuais para eco parques tecnológicos - Salvador, Douglas Santos (2018)
Technology parks promote science, technology, and innovation through elements such as universities, research laboratories, high technology companies, incubators, infrastructure service providers, among others. This research proposes guidelines and technical recommendations to be applied in the design of these projects based on architectural and urban strategies that aim at greater environmental sustainability and the mitigation of the impacts generated by anthropic action. For this, were identified sustainable strategies for the variables of this study from the methods and systems of certification and environmental orientation that provide guidelines in this sense, verified parameters for territorial occupation with higher environmental quality, norms with indicators of urban sustainability, evaluated the potential to apply a current concept central to sustainable development - the food, energy and water nexus - and analyzed technological parks in operation or in the implementation phase that somehow propose to minimize environmental impacts. The following analysis variables were considered: natural resources, environmental comfort, energy, waste and urban insert. The results showed that for the effective caracterization of a eco-technological park, it is necessary to generate environmentally more advantageous and beneficial situations that only the use of design premises that function as mitigating measures. They also demonstrate that eco-technology parks should aim for the highest possible self-sufficiency and, therefore, are opportune for the adoption of strategies that incorporate the food-energy-water nexus, as the approach Roof Mosaic. From this perspective, this study contributes to the elaboration of the Nexus Emission Index (NEI), which evaluates the potential of CO2 emissions avoided by these vectors and serves as an instrument of verification and prioritization in the final decision making by those responsible for the projects of these enterprises. From this, a technical-conceptual repertoire was systematized with 61 guidelines and technical recommendations for the design and characterization of eco-technology park.